Treasures of the Elite of the Bulgharian Ulus of the Golden Horde - Rudenko K.A. (Золотоордынское обозрение)
Research objectives: To analyze the materials of the most famous hoards of the Golden Horde era found on the territory of the Bulgharian ulus on the basis of a comprehensive analysis. To identify the coincidence of jewelry that they contained. To determine the similarities and differences with other finds from this territory, as well as to identify the possible place of their manufacture and their connection with archaeological sites. Research materials: Preserved jewelry from the Karasham and Juketau hoards. The former was found in 1950 near the village of Karasham in the Zelenodolsk district of the Republic of Tatarstan. The latter was found in 1924 on the outskirts of the city of Chistopol in the Chistopol district of Tatarstan, next to the medieval settlement – the remnants of the Bulgharian city of Juketau which existed from the tenth to early fifteenth centuries. In addition to jewelry, both hoards contained silver and gold coins which made it possible to determine the time when these hoards were buried. The hoard near the village of Karasham was deposited at the beginning of the fifteenth century. The Juketau hoard was deposited in the 1350–70s. Both hoards are not fully preserved. The author carefully studied jewelry from the hoards that are now stored in the National Museum of the Republic of Tatarstan, as well as in the State Hermitage. Items from other hoards of this time found in the territory of Tatarstan, as well as published materials from private collections, are also involved in the study. Results and novelty of the research: The author investigated, for the first time ever, the surviving part of the Karasham hoard, including jewelry that was not considered in the studies of other scholars. A comparative analysis of the jewelry was carried out. To find out the distribution of such jewelry, a search was made for analogies and similar jewelry that was found in other hoards as well as among the archaeological materials from settlements of the Golden Horde era. It was found that the most significant part of the Karasham hoard’s jewelry was made in the jewelry workshops of the city of Bolghar, and partly by the jewelers from other craft centers in the Golden Horde. It should be noted that jewelry was made in both gold and silver in Bolghar. The most popular products were bracelets with images of the lion’s muzzle on the ends of objects, as well as bracelets with stylized images made using niello. Such bracelets were found both in the hoard from Karasham and from Juketau. The existence of jewelry workshops in Bolghar is also confirmed by archaeological excavations. In the second half of twentieth and at the beginning of the twenty-first centuries, archaeologists found several jewelry workshops in the central part of the city dated to the fourteenth century. Crucibles, jewelry tools, and more than hundred foundry molds were discovered here. The author assumes that a famous jeweler from Bolghar named Shagidulla worked here at the beginning of fourteenth century. It was also found that the hoard from Karasham was most likely collected by several generations of the same family. In contrast, the hoard from Juketau was a personal treasure.